Analisis Perilaku dan Teritori Pengguna Gedung F Kampus Institut Teknologi Kalimantan - Natasya; Dewi, Tiara Rukmaya; Putra, Rullianor Syah (SPECTA Journal of Technology, 2023)
Students need space as a place to gain knowledge and broader insights. Kalimantan Institute of Technology (ITK) is a campus or a place for students to gain knowledge and improve their soft skills with high quality. However, this has not been fully supported by good accommodation. Students are not satisfied with the accommodation provided, such as the small canteen size, which does not have a waiting room. This paper tries to discuss this phenomenon by raising a case to identify the types of territory and territorial behavior in the F ITK Building, namely the inner space created by the occupants and the space used by the occupants as an effort to fulfill their daily activities and intends to obtain design recommendations. room in Building F ITK. The approach to analysis emphasizes the need for an understanding based on an explanation of an issue or event so that it can further study the complexity of the relationship between humans, the environment, and behavior. The data collection method used was observation (place-centered mapping) and distributing questionnaires to students who use the room in Building F ITK. In addition, interviews were also conducted to dig deeper into the trends in the results of the questionnaire. This study's results are expected to optimize the need for inner space, which has been the center of student activity. The form of optimizing the use of space is described in the design recommendations in accordance with the behavioral tendencies and territories of students as space users.